Diseño y construcción de un prototipo mecánico para la modelación física de la actividad sísmica de la ciudad de Bogotá D.C basado en el estudio de microzonificación sísmica (2023)
This research is based on the need for universities to develop new experimental methods with the aim of improving student learning in classrooms. Based on this, a vibrating table has been designed and built for simulating earthquakes in scaled structural models. This table has the capacity to represent the dynamics and behavior of structures when subjected to seismic movements. Its main purpose is to support the educational process of university students in related subjects, as well as in future research projects that require this tool. The design was carried out by means of a historical reconstruction of research from other institutions that use this type of tables and technological developments in their academic spaces. It has been found that numerous institutions, both nationally and internationally, employ this learning method. Not only vibrating tables are used, but also technologies like augmented reality, which allow for the verification of structures and materials, not only in the student realm but also in the professional sphere. Therefore, it is important to implement these technologies in educational institutions.